(3GdESYGa HTQM CHjGJ GdbGaj hGdcTGas - (3NVQ Hf YWGA Gddg GdehUdj,J (B1007 (3g` s; (3GdehUdj , NVQ Hf YWGA Gddg,J (B1007 (3g` s
(3ChdgG (B:s
(3Gddge HCcJTGa VGHI GdGhgGe TjehS GdYdhe CeG HYO aEf CaVd eG jgJe HJMUjdg hjYJfi HGA LeGdg hJaUjdI eYQaI eG Hg GdEYLGR hGdYKhQ Ydi eJOGhdGJ GdCdaGX s
(3BNQgG (B:s
(3JfhW dfG MH GdMjGI fahSfG SaGgG hjCJi GdehJ ef MjK dG JOQi Je GdLRA GdChd ef GdGSYGa s
(3HgG fXGe GdJYbjHIs
(3CJe JCdjaI SfI (B994 (3g`s
(3hgj eMdGI HGdPgH hGdCdhGfs
(3hHChdg agQS s
(3hgj fSNI NRGFfjIs
(3HQSe CHj jMji eMeO Hf GdMSfs
Keywords: (3eJaQbGJs